A atuação das equipes multiprofissionais para viabilizar os direitos da pessoa idosa: estudo nas instituições de longa permanência para idosos de João Pessoa/ PB - Costa, Priscila de Almeida da (2017)
The process of demographic and epidemiological transition currently experienced by the Brazilian people reveals the intense and heterogenous growth in the aging in the country. In order to study such phenomenon, it is essential to understand the specificity of the needs of the aged, as well as social, economic, historical and cultural factors exerting influence in that context. To meet the expressions of the social question raised by the increase in population aging, the State has set norms through laws, regulations and decrees. This study aimed at analyzing what is the contribution from multiprofessional teams to the feasibility of the social rights of elderly people living the Long-Term Institutions for the Elderly in Joao Pessoa, PB. It is a quantitative-qualitative, field and descriptive research, done with a sample of 17 professionals with higher education, including: social worker, nurse, physical therapist, medical doctor, nutritionist, pedagogue and psychologist who make up the multiprofessional teams in three entities in Joao Pessoa/PB: Casa da Divina Misericordia, Instituicao Espirita Nosso Lar and Vila Vicentina Julia Freire. The duration of the research occurred between the months of July and September 2016. The tools and techniques used for data collection were: participant observation; written semi structured interview with questions related to the profile of the surveyed subjects, the social rights of elderly people and the performance of the multiprofessional team. Also bibliographic survey and documental research were used. With respect to data processing and analysis, we proceeded by allocating the quantitative data in charts and tables elaborated through Microsoft Office Excel 2010. The qualitative data were treated through critical analysis of the testimony fragments in light of the selected theoretical corpus. The research was approved by the Research Ethics Committee of the Health Sciences Center of UFPB, and it respected the ethical aspects through all its execution, since the subjects agreed to participate voluntarily through signing the Informed Consent Form. In the end, the survey evidenced lack of responsibility from the State to the institutionalized elderly, such responsibility being transferred to the third sector. The results also revealed the scant knowledge of social legislation by the health professionals working in the surveyed ILPIs. Furthermore, persistent lacunae were detected regarding the continuous education of the teams about constitutional rights of the elderly, impacting their performance. As to the processing of the demands, there is no systematic organization, meaning that those professionals solve such issues as they occur in the execution of the actions. The data also pointed out that the contribution of the multiprofessional teams is related to the articulations and the forwarding to the organs that meet the demands from the residents, besides aiding the bond between family and the institutionalized elderly. Lastly, the survey signalized that the contribution of the multiprofessional teams to the feasibility of the rights of the elderly is still inconsistent, mirroring the incoherent social protection network designed to that segment.